Quizizz and its application in learning of the students of the foreign language professional career - Robles-Gonzales, Hillary Eddy (2022)
The insertion of the various educational platforms has facilitated the virtual teaching process. One of the most used tools is Quizizz in feedback and it can generate different learning styles. The present research aims to describe the perception of Quizizz as part of connectivism in higher education at the Jorge Basadre Grohmann National University in Tacna-Peru in the academic year 2021. The type of research is descriptive, while the method used is inductive. For its execution, a virtual form made up of 13 questions was used, considering 168 students of the Foreign Language specialty of the Faculty of Education as a sample of this study. The results show that the Quizizz platform encourages students to connect with their learning in a positive way. In conclusion, students consider technological tools relevant to achieve optimal learning, since technology is already part of their learning process, and with the teacher's guidance, they can achieve a dynamic class, where they actively participate.